In Situ Pre-Treatment of Vascularized Composite Allografts With a Targeted Complement Inhibitor Protects Against Brain Death and Ischemia Reperfusion Induced Injuries - Lei, Biao; Sleiman, M. Mahdi; Cheng, Qi; Tu, Zhenxiao; Zhu, Peng; Goddard, Martin; Martins, Paulo N.; Langerude, Logan; Nadig, Satish; Tomlinson, Stephen; Atkinson, Carl (Frontiers in Immunology, 2021)
Introduction: Donor brain death (BD) is an unavoidable component of vascularized composite allograft (VCA) transplantation and a key contributor to ischemia-reperfusion injury (IRI). Complement is activated and deposited within solid organ grafts as a consequence of BD and has been shown to exacerbate IRI, although the role of BD and complement in VCA and the role it plays in IRI and VCA rejection has not been studied. Methods: BD was induced in Balb/c donors, and the VCA perfused prior to graft procurement with UW solution supplemented with or without CR2-Crry, a C3 convertase complement inhibitor that binds at sites of complement activation, such as that induced on the endothelium by induction of BD. Following perfusion, donor VCAs were cold stored for 6 hours before transplantation into C57BL/6 recipients. Donor VCAs from living donors (LD) were also procured and stored. Analyses included CR2-Crry graft binding, complement activation, toxicity, injury/inflammation, graft gene expression and survival. Results: Compared to LD VCAs, BD donor VCAs had exacerbated IRI and rejected earlier. Following pretransplant in-situ perfusion of the donor graft, CR2-Crry bound within the graft and was retained post-transplantation. CR2-Crry treatment significantly reduced complement deposition, inflammation and IRI as compared to vehicle-treated BD donors. Treatment of BD donor VCAs with CR2-Crry led to an injury profile not dissimilar to that seen in recipients of LD VCAs. Conclusion: Pre-coating a VCA with CR2-Crry in a clinically relevant treatment paradigm provides localized, and therefore minimally immunosuppressive, protection from the complement-mediated effects of BD induced exacerbated IRI.